Design and Optimization of a PMSM for Obtaining High-Power Density and High-Speed - Boztas, Gullu; Yıldırım, Merve; Aydogmus, Omur (My University, 2020)
It is very important to obtain high power in a small volume for many applications. Especially, power/weight (W/kg) ratio needs to be well balanced in electric and aircraft vehicles, military and robotic applications. High power density can usually be obtained with a magnet-assisted motor. However, it is very difficult in terms of design for the motor to have both high power and low weight. Therefore, motor design should be supported by a good optimization. In this study, Multi-Objective Genetic Algorithm (GA) is used to obtain high power and low weight. Thus, targets are achieved by both optimizations at the same time. Rotor inner diameter, stack length, magnet insert, magnet thickness, and magnet angle are optimized in this paper. The motor is designed as 24 slots and 16 poles. 1100 generations are obtained by optimization and it has been decided that 1092th generation is the most suitable motor. Hence, motor having approximately 8 kW output power and 1.3 kg rotor mass is designed. The motor efficiency is obtained about 97% when friction and ventilation losses are neglected. As a result, it is observed that designed PMSM with high-power density and high speed can be used in the robotic and military applications.
Keywords: Optimization; Genetic Algorithm; Permanent Magnet Synchronous Motor; High Power Density; Motor Design